Pengaruh Independensi, Kompetensi, dan Obyektivitas Auditor Internal terhadap Kualitas Hasil Pemeriksaan (Studi Empiris pada Inspektorat Provinsi DKI Jakarta) - Muhamad Sobar; Suratno .; M Yusuf (JURNAL CITRA WIDYA EDUKASI, 2019)
This study aimed to examine the effect of independence, competence and objectivity internal auditor of the quality of examination on Inspectorate of Jakarta Province. Variable of internal auditor independence elaborated into two indicators, ie the auditor independence in fact and auditor independence in attitude and appearance (independence in appearance). Variable of competence elaborated into three indicators, ie attitude, knowledge and skill. Variable of objectivity elaborated into three indicators, ie the auditor neutrality, accuracy and consistency of the auditor attitude in the assignment and the auditor attitude to avoid conflict of interest. Variable of quality of examination result elaborated into two indicators, ie the quality of reporting and the quality of follow-up examination. The population in this study is an internal auditor at the Inspectorate of Jakarta Province who occupying Specific Functional Job consisting of auditor and Supervision Affairs of Regional Government (P2UPD). The method used in this research is multiple linear regression. The result of this study indicate that partial independence does not significantly affect the quality of examination result, competence and objectivity while significantly influence the quality of examination result. The result also showed that the independence, competence and objectivity simultaneously affect positive and significant impact on the quality of the examination result.